Analyzing Argumentative Texts Produced by English Education Master's Students at UIN Syarif Hidayatullah Jakarta - Nazhifah, Naurah; Hidayat, Didin Nuruddin; Alek, Alek; Fatwa Mulyati, Yatni; Baker, Shirley (Inspiring: English Education Journal, 2024)
This research investigates the grammatical construction and common logical problems in argumentative essays produced by Master of English Education students at UIN Syarif Hidayatullah Jakarta. This study utilized a qualitative research framework and content analysis as the design. The data collection involves a detailed syntactical analysis, facilitated by Shang’s syntax tree generator, with the researcher actively engaged in the evaluation and categorization of grammatical and logical elements. The main arguments are identified, and connections to the overarching thesis are established. Systematic coding is applied to categorize findings, encompassing sentence structure, evidence usage, tone, logical connectives, cohesions, counterarguments, and identification of logical fallacies. Findings reveal notable technical errors in sentence construction, especially in constructing complex sentences. Moreover, difficulties in understanding the appropriate genre in argumentative writing and logical errors in expressing opinions and drawing conclusions are identified. This study discovered that students encounter difficulties in maintaining a coherent and logically sound progression of ideas throughout their essays.